Polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and chlorinated pesticides in background air in central Europe – investigating parameters affecting wet scavenging of polycyclic aromatic hydrocarbons - P. Shahpoury; G. Lammel; A. Holubová Šmejkalová; J. Klánová; P. Přibylová; M. Váňa (Atmospheric Chemistry and Physics, 2015)
Concentrations of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and chlorinated pesticides (CPs) were measured in air and precipitation at a background site in central Europe. ∑ PAH concentrations in air and rainwater ranged from 0.7 to 327.9 ng m−3 and below limit of quantification (< LOQ) to 2.1 × 103 ng L−1. The concentrations of PCBs and CPs in rainwater were < LOQ. ∑ PCB and ∑ CP concentrations in air ranged from < LOQ to 44.6 and < LOQ to 351.7 pg m−3, respectively. The potential relationships between PAH wet scavenging and particulate matter and rainwater properties were investigated. The concentrations of ionic species in particulate matter and rainwater were significantly correlated, highlighting the importance of particle scavenging process. Overall, higher scavenging efficiencies were found for relatively less volatile PAHs, underlining the effect of analyte gas-particle partitioning on scavenging process. The particulate matter removal by rain, and consequently PAH wet scavenging, was more effective when the concentrations of ionic species were high. In addition, the elemental and organic carbon contents of the particulate matter were found to influence the PAH scavenging.